Creating digital branding and a visual identity for Edupark Cocoa Bigaran - Prihatin Dwihantoro; Dwi Susanti; Lintang Muliawanti; Annis Azhar Suryaningtyas; Fadillah Sandy; Alan Kusuma; Rizka Rahmawati; Tiffani Anggi Amelia; Della Anindita Putri (Universitas Muhammadiyah Magelang, 2024)
The Bigaran Cocoa Edupark business combines aspects of education and tourism with a focus on the chocolate industry. However, the Bigaran Cacao Edupark tour which was just pioneered in 2022 does not yet have a visual identity and is not widely known by the wider community. This community service activity aims to improve partners' skills related to the program related to digital branding of tourism and designing the visual identity of Bigaran Cocoa Edupark. This program is carried out with a participatory method which is focused on 1) training on tourism digital branding, and 2) designing the visual identity of Bigaran Cocoa Edupark. The implementation of activities is starting with observation, socialization, visual identity design, digital branding training and assistance, as well as monitoring and evaluation. The result of this program is the establishment of Instagram and Tiktok social media accounts accompanied by a time schedule content for 1 year as a promotional media. In addition, 1 set of graphic standard manual visual identity of Bigaran Cocoa Edupark consisting of logo, packaging and business card was also created along with the grant of chocolate molding goods.